2012
DOI: 10.1021/ef300106z
|View full text |Cite
|
Sign up to set email alerts
|

Composition Analysis and Viscosity Prediction of Complex Fuel Mixtures Using a Molecular-Based Approach

Abstract: The automobile industry currently faces the challenge of developing a new generation of diesel motor engines that satisfy both increasingly stringent emission regulations and reduces specific fuel consumption. The performance of diesel engines, seen in terms of emissions and specific fuel consumption, generally improves with increasing fuel-injection pressure. The design of the next generation of diesel fuel injection systems requires the knowledge of the thermophysical properties, in particular viscosity, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 51 publications
0
58
0
Order By: Relevance
“…Some limitations were identified when the model was applied to asymmetric mixtures of methane with toluene. Aquing et al [26] have performed composition analysis and viscosity predictions of complex fuel mixtures using an anisotropic united atom force-field approach. Recently, coarse-grained molecular models have been used successfully to predict the viscosity of medium size n-alkanes [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Some limitations were identified when the model was applied to asymmetric mixtures of methane with toluene. Aquing et al [26] have performed composition analysis and viscosity predictions of complex fuel mixtures using an anisotropic united atom force-field approach. Recently, coarse-grained molecular models have been used successfully to predict the viscosity of medium size n-alkanes [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Insofar as quantitative predictions can be obtained, such techniques represent an interesting manner to predict property values for complex fluids, all the more when pressure and temperature conditions make experiments hazardous. For instance, we proposed works dealing with simulations of gasoline and diesel fuels for pressure and/or temperature conditions encountered within injectors, and showed that molecular simulation is appropriate to overcome limits of experimental devices . Similarly, numerical simulations are interesting tools when the considered molecules are toxic for human, which is typically the case of systems containing H 2 S .…”
Section: Computational Methods and Resourcesmentioning
confidence: 99%
“…At high pressures, compositional variance between fuels can lead to significant differences in viscosity. For example, the viscosity of two different diesel fuels reported by Aquing et al [13] and Schaschke et al [12] at 323 K differ by more than 120% at 1,800 bar and 200% at 2,400 bar. Models fit to viscosity data for one diesel sample cannot be expected to accurately represent the viscosity of another diesel of different composition.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, several researchers demonstrated advantages when incorporating advanced equations of state (EoS), such as the Perturbed-Chain Statistical Associating Fluid Theory (PC-SAFT) within CFD [22][23][24]. Given that complex mixtures (e.g., diesel and biodiesel fuels, crude oils, bitumens, heavy oils) are often composed of hundreds of different compounds [13,[25][26][27][28][29], CFD simulation of every fuel compound would be computationally intensive. Often, a smaller number of components are chosen as a surrogate to closely match the thermophysical properties of the mixture [13,[30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%